Ethanolic extract of Azadirachta indica as a biological control of Spodoptera frugiperda larvae (J.E. Smith) (Lepidoptera: Noctuidae) (FAVE Sección Ciencias Agrarias, 2025)
The objective of this study was to evaluate the effectiveness of an ethanolic extract of neem leaves in the biological control of the larval stage of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae). S. frugiperda larvae were collected and size sorted. A neem leaf extract was prepared by drying, grinding, and extraction with 90% ethanol. Secondary metabolites were qualitatively identified, and azadirachtin was quantified by HPLC-UV, and a calibration curve was constructed. Larvae were exposed in vitro to different concentrations of the extract (0 %, 25 %, 50 %, 75 %, 100 %) in a completely randomized block design with four replicates. Larval mortality was recorded sequentially, and data were analyzed using ANOVA and Fisher's LSD test. Phytochemical screening of the neem extract revealed the presence of triterpenes/sterols, alkaloids, flavonoids/anthocyanins, and phenols. HPLC-UV analysis quantified azadirachtin, with a highly linear calibration curve (R²=0.99). Morphological characterization of larval S. frugiperda showed distinctive features under stereomicroscopy. Mortality assays demonstrated that neem extract is effective against larvae, especially in the early instars. ANOVA indicated significant differences in mortality between neem treatments and the control, with no significant differences between concentrations ranging from 25% to 100%. Neem extract, rich in bioactive compounds and with confirmed azadirachtin, proved effective in controlling S. frugiperda, even at low concentrations, highlighting its potential as a biopesticide.